Evaluation of Conventional Root Canal Treatment for Healing of Periapical Pathosis of Nonvital Teeth - Hossain, Md Ismail; Parveen, Monira; Choudhury, Md Nahid Khurram; Wakia, Tasnim; Uddin, Farid; Rahman, Md Shoyeb (TAJ: Journal of Teachers Association, 2020)
Background: Root canal Therapy is one of the procedures for the management of nonvital tooth with periapical lesion. The principle of this therapy is the complete sterilization of the total pulp canal space thereby healing of the periradicular lesion. Objectives: This experimental study assessed the clinical and radiological outcome of root canal treatment for nonsurgical management of nonvital teeth with periapical lesion. Materials and Methods: A total number of 40 infected teeth with periapical lesion were treated by conventional root canal treatment. Irritants from the root canal system was removed by mechanical instrumentation( Crown down Technique), chemical irrigation with NaOCL and by using Calcium Hydroxide as intracanal medicaments and fluid tight obturation both apically and coronally resulting repairs of inflamed periradicular tissues. The protocol for follow up examination will be 3, 6 and 12 months post operatively. At the time of follow up examination a standard follow up chart will be maintained. Results: Among 40 cases 32 cases could be treated as acceptable as their responses were good both clinically and radiologically and 5 patients came back with some complications among them 3 cases were uncertain and 2 cases were unacceptable. Conclusion: It was concluded that conventional root canal treatment reduced clinical signs and symptoms successfully in teeth with periapical lesion and radiologically. TAJ 2020; 33(1): 25-30